2020
DOI: 10.1371/journal.pone.0234039
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome inhibition attenuates sepsis-induced platelet activation and prevents multi-organ injury in cecal-ligation puncture

Abstract: Sepsis is characterized by organ dysfunction due to a dysregulated immune response to infection. Currently, no effective treatment for sepsis exists. Platelets are recognized as mediators of the immune response and may be a potential therapeutic target for the treatment of sepsis. We previously demonstrated that NLRP3 inflammasome activation in sepsis-induced activated platelets was associated with multi-organ injury in the cecal-ligation puncture (CLP) rat model of sepsis. In this study, we tested the hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 36 publications
3
38
0
Order By: Relevance
“…Moreover, treatment of diabetic rats after stroke with MCC950 ameliorated cognitive function, vascular permeability, and neurovascular remodeling 114 . More recently, it has been found that sepsis-related endothelial dysfunction was also improved with MCC950 intervention in in vivo and in vitro models 115,116 . Additionally, CY-09, OLT1177, 3,4-methylenedioxy-β-nitrostyrene (MNS), N-[3′,4′-dimethoxycinnamoyl]-anthranilic acid (Tranilast), and oridonin are also specific inhibitors of NLRP3 inflammasome 33,117 .…”
Section: Other Anti-inflammatory or Antioxidant Drugsmentioning
confidence: 99%
“…Moreover, treatment of diabetic rats after stroke with MCC950 ameliorated cognitive function, vascular permeability, and neurovascular remodeling 114 . More recently, it has been found that sepsis-related endothelial dysfunction was also improved with MCC950 intervention in in vivo and in vitro models 115,116 . Additionally, CY-09, OLT1177, 3,4-methylenedioxy-β-nitrostyrene (MNS), N-[3′,4′-dimethoxycinnamoyl]-anthranilic acid (Tranilast), and oridonin are also specific inhibitors of NLRP3 inflammasome 33,117 .…”
Section: Other Anti-inflammatory or Antioxidant Drugsmentioning
confidence: 99%
“…Many studies have found that inhibiting the activation of NLRP3 inflammasome has a protective effect on septic animals ( 24 ). In particular, the NLRP3 inhibitor MCC950 attenuates multi-organ injuries in septic rats ( 25 ), highlighting the potential of using NLRP3 inhibitors in the treatment of sepsis.…”
Section: Types and Activation Of Inflammasomes In Sepsismentioning
confidence: 99%
“…In vivo , lack of Casp1 (instead of CASP11) protects mice from EprJ-induced lethality associated with the reduction of DIC biomarkers in blood ( 30 ). In polymicrobial sepsis induced by cecal ligation and puncture (CLP), inhibiting the activity of CASP1 with the NLRP3 inhibitor MCC950 also reduces platelet activation in rats ( 25 , 55 ). These animal studies suggest that CASP1 has a potential role in regulating septic coagulation in mice and rats.…”
Section: Modulation and Function Of Inflammasome In Coagulationmentioning
confidence: 99%
“…Similar results were observed using interleukin 1 receptor antagonist (IL-1ra) [ 13 ], corroborating the importance of this pathway. Multiple early life events in the lung have been associated with NLRP3 activation, including viral and bacterial infections, Bronchopulmonary dysplasia and even septic events, which have been associated with increased susceptibility to later disease [ 13 , 45 , 46 , 47 ]. Perhaps targeting NLRP3 during these early life events may provide a common therapeutic pathway for controlling long term sequelae that are often observed later in these children, including childhood asthma.…”
Section: Discussionmentioning
confidence: 99%